Research Competencies and their Analysis in the Field of Educational Technology Through E-Learning - Márquez Silva, Fatima (2025)
Research competencies are conceptually known as skills that allow for a scholarly interaction between theory and practice involved in formative processes. Qualitative research through systematic literature review was conducted to analyze the relationship that may exist between e-learning and research competency, as this field has not been sufficiently explored by including trends in educational innovation. The strategy involved searching specialized databases using Boolean formulas, wildcards, and truncators, with the purpose of constructing a new instructional proposal. The results demonstrated that the majority of studies have focused on the development of conceptual and procedural levels, lacking an attitudinal level in the acquisition of research competencies. As part of the discussion, the terms ability and competence should be recognized and differentiated, since they are mixed in the state of knowledge. It was concluded that it is necessary to define a model of research competencies that includes all levels of mastery: conceptual, procedural and attitudinal, for the integral development of these competencies.